ASSISTANCE TO ANTI-BULLYING CADRES (PEER TEACHING METHOD) ON KNOWLEDGE AND ATTITUDES IN PREVENTING TEENAGE BULLYING - Atiul Impartina; Dadang Kusbiantoro; Dian Nurafifah (Universitas Muhammadiyah Lamongan, 2024)
Background: Bullying is an incident that often occurs in everyday life among teenagers, especially at school, even the Minister of Education, Culture, Research and Technology said that the incidence of bullying in Indonesia is still very high, there are 24.4% of students in Indonesia experiencing this incident. In 2020, KPAI recorded 119 cases of child bullying, compared to the previous year there was an increase of 30-60 cases per year. In Lamongan Regency in 2020 there were 22 cases, while in 2021 there was an increase to 42 cases of violence. Objectives: The aim of the research is to determine the effect of mentoring students as anti-bullying cadres using the peer teaching method on knowledge and attitudes in preventing teenage bullying. Method: Evaluation is carried out by comparing work results before and after the intervention is given. Results: The results of the training showed that there was an increase in participants' understanding of bullying prevention (100%), and there was an increase in participants' ability to identify and problem solve bullying cases (83%). Conclusion: Education is needed for students in preventing bullying